Boric acid inhibits germination and colonization of Saprolegnia spores in vitro and in vivo. - Shimaa E Ali; Even Thoen; Øystein Evensen; Ida Skaar (PLoS ONE)
Saprolegnia infections cause severe economic losses among freshwater fish and their eggs. The banning of malachite green increased the demand for finding effective alternative treatments to control the disease. In the present study, we investigated the ability of boric acid to control saprolegniosis in salmon eggs and yolk sac fry. Under in vitro conditions, boric acid was able to decrease Saprolegnia spore activity and mycelial growth in all tested concentrations above 0.2 g/L, while complete inhibition of germination and growth was observed at a concentration of 0.8 g/L. In in vivo experiments using Atlantic salmon eyed eggs, saprolegniosis was controlled by boric acid at concentrations ranging from 0.2-1.4 g/L during continuous exposure, and at 1.0-4.0 g/L during intermittent exposure. The same effect was observed on salmon yolk sac fry exposed continuously to 0.5 g/L boric acid during the natural outbreak of saprolegniosis. During the experiments no negative impact with regard to hatchability and viability was observed in either eggs or fry, which indicate safety of use at all tested concentrations. The high hatchability and survival rates recorded following the in vivo testing suggest that boric acid is a candidate for prophylaxis and control of saprolegniosis.